PENGARUH ASSESMEN PORTOFOLIO DAN USIA TERHADAP PENINGKATAN KEMAMPUAN KEAKSARAAN BAGI WARGA BELAJAR KEAKSARAAN FUNGSIONAL - Abdul Kahar (Jurnal Ilmiah Visi, 2010)
The objective of the research is to know the differences in reading and writing achievement between non-formal participants with conventional evaluation and those with portfolio evaluation treatment and between those of 15 years age or under and those of above 15 years age or above, and the interaction type of evaluation and age variable. The design of this research used Factorial Experiment 2X2. Research population covered all of those who learnt at Community Learning Activities Center in Makassar. Eighty respondents were selected by multi stage random sampling. Data on reading and writing learning achievement were obtained using a test and analyzed using descriptive statistic analysis and inferential analysis with Multivariate Analysis of Variants (two-way MANOVA). The research conducted in 2005 indicates that there are significant differences in reading and writing achievement between non-formal participants with conventional evaluation and those with portfolio evaluation treatment and between those of 15 years age or under and those of above 15 years age or above. These findings imply that in implementing functional literacy program, the application of different evaluation models to different age group need to be considered.